KINERJA PENYULUH PERTANIAN SEBAGAI PENYEBAR INFORMASI FASILITATOR DAN PENDAMPING DALAM PENGEMBANGAN SAPI BALI (Bos sondaicus) DI KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - Eko Harianto .; Surahmanto -; Putu Arimbawa (Fakultas Pertanian Universitas Halu Oleo, 2014)
The aims of this study were to analyze the influence of extension workers demographic character and character of the farmers who were responsible guidance of the extension workers on extension workers performance as disseminator of information, facilitator, and guidance, and to analyze relationship between the extension workers performance as disseminator of information, facilitator, and guidanceand the achievement of Bali cattle development program. Data were collected by survey method with direct interview with respondents, both extension workers and the farmers who were responsible guidance of the extension workers by using questionnaire. Data were analyzed by using descriptive analysis, multiple regression with enter and stepwise method, and spearman ranks correlation analysis. The results showed that factor that significantly influenced (P < 0,05) performance of agricultural field extension workers as disseminator of information, facilitator, and guidance in Bali cattle development program was the non formal education of extension workers. The extension worker’s age, formal education, andexperience were not influence the extension worker’s performance. In addition age, formal education, land ownership, and farming experience of the farmers who were responsible guidance of the extension workers also didn’t influence extension worker’s performance. The extension workers performance had positive corelation (P < 0.01) with the achievement of Bali cattle development program. Keywords: agricultural field Extension workers, Performance, Bali Cattle